Brigham Fracture Intervention Team Initiatives for Hospital Patients with Hip Fractures: A Paradigm Shift - Julie Glowacki; Mitchel B. Harris; Josef Simon; John Wright; Nikheel S. Kolatkar; Thomas S. Thornhill; Meryl S. LeBoff (International Journal of Endocrinology)
We designed, implemented, and revised the Brigham Fracture Intervention Team (B-FIT) initiatives to improve in-hospital care of fracture (Fx) patients. Effectiveness was evaluated for 181 medical records of 4 cohorts in four successive years of consecutive patients who were admitted with a fragility hip Fx. The Discharge Initiative (DI) (computer-based) includes 1200 mg calcium and 1000 IU vitamin D3 daily. The Admission Initiative (AI) was introduced one year later with reminders for serum 25OHD measurement, initiation of daily calcium (1200 mg) and vitamin D (800 IU), and an order for Endocrinology consultation, with an amendment for a computer-assisted reminder and a dose of D2 (50 000 IU). Initially, the computer-based DI was more effective (67%) than the surgeon-driven AI (33%, 𝑃<.001). After introduction of a computer-assisted reminder, AI effectiveness increased to 68%. The marked prevalence of vitamin D insufficiency reaffirms the importance of incorporating vitamin D recommendations in Fx care pathways.